Russian Federation Diagnostic Review of Consumer Protection in Financial Services : Comparison against Good Practices - World Bank (World Bank, Washington, DC, 2017)
Over the last decade, consumer credit in the Russian Federation has expanded from almost nothing to 9.2 percent of GDP in 2008, at 84 percent average annual growth in 2003-2008 year for five years. Yet, the increases have been uneven throughout the Russian population: more than 40 percent are still financially excluded and only 16 percent have bank accounts. A 2008 survey found that Russian consumers had low levels of financial literacy and lacked awareness of their rights as financial consumers. Three-quarters of the survey's respondents said they would like to receive financial education in order to protect themselves financially and plan for the future. Similar trends of the booming credit markets amid significant gaps in financial literacy around the world have contributed to the global financial crisis of 2008 and emphasized the importance of consumer protection and financial education programs for the long-term health of the financial sector. Responding to a request from Russian authorities, the World Bank conducted a diagnostic review to help Russia design an effective consumer protection and financial literacy framework. This review, presented in two volumes, outlines the key findings and recommendations in Volume I, and analyzes the existing rules and practices in Russia, in comparison with international good practices – in Volume II. Banking, non-bank credit, securities, insurance, private pensions, and credit reporting segments are covered.